1989
DOI: 10.1002/jcb.240400311
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of phospholipids and enzymes involved in PAF‐acether metabolism

Abstract: The biosynthesis of platelet-activating factor (PAF-acether or 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine) through the remodeling pathway was investigated at the subcellular level in two different cell lines. In human neutrophils, plasma membrane was isolated not only from granules, but also from internal membranes related to endoplasmic reticulum. Interestingly, the latter exhibited enhanced acetyltransferase upon neutrophil stimulation with ionophore A23187. A similar study was undertaken on the tumor st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

1991
1991
2001
2001

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 43 publications
0
6
0
2
Order By: Relevance
“…We employed microsomes from unstimulated cells as our acetyltransferase source and evaluated the effect of various recombinant, constitutively activated MAP kinases on acetyltransferase activity. It has been recognized for some time that the acetyltransferase is localized in an internal membrane source (32,33), and although the compartment has not been unequivocally determined, it has been suggested that it resides in either the tertiary granule or endoplasmic reticulum membranes (34). Regardless of the exact source, microsomal fractions were found to contain the highest specific activity of acetyltransferase activity.…”
Section: Activation Of Map Kinase(s) and Acetyltransferase By Tnf-␣ mentioning
confidence: 99%
“…We employed microsomes from unstimulated cells as our acetyltransferase source and evaluated the effect of various recombinant, constitutively activated MAP kinases on acetyltransferase activity. It has been recognized for some time that the acetyltransferase is localized in an internal membrane source (32,33), and although the compartment has not been unequivocally determined, it has been suggested that it resides in either the tertiary granule or endoplasmic reticulum membranes (34). Regardless of the exact source, microsomal fractions were found to contain the highest specific activity of acetyltransferase activity.…”
Section: Activation Of Map Kinase(s) and Acetyltransferase By Tnf-␣ mentioning
confidence: 99%
“…The process may be regulated at the level of either lipid synthesis or at the dedicated lysoglycerophosphate acetyltransferase and cholinephosphotransferase [25]. In contrast, the stimulated PAF synthesis via the remodelling pathway [26] is induced by cellspecific stimuli such as the inflammatory mediator thrombin [23]. It can be triggered non-specifically by Ca# + ionophores.…”
Section: Discussion Paf Synthesis and Transportmentioning
confidence: 99%
“…It involves a phospholipase A # -catalysed release of arachidonate from the sn-2 position of an alkyl-PC, yielding the PAF-precursor lyso-PAF and the eicosanoid precursor arachidonic acid. Lyso-PAF is converted into PAF by the esterification with acetate, which is catalysed by a specific acetyl-CoA : lyso-PAF acetyltransferase [26].…”
Section: Introductionmentioning
confidence: 99%
“…Upon transfer of 1-0-alkyl-2-acyl-GPC from the endoplasmic reticulum to the plasma membrane, the sn-2 position could be removed by hydrolysis to produce lysoPAF. The most efficient pathway for PAF synthesis to occur would be through similar topographical locations for the acetyltransferase and the enzyme responsible for the hydrolytic activity producing lysoPAF from l-O-alkyl-2-acyl-GPC (Record et al 1989). It has been widely accepted that the enzyme responsible for this activity is a phospholipase-A2 (PLA 2 ; EC 3.1.1.4) (Waish et al 1981;Swendsen et al 1983;Pinckard et al 1988;Bauldry et al 1991).…”
Section: Transfer Proteinsmentioning
confidence: 99%